Shaping Economic Growth of Thailand through Crude Oil Dynamics: Role of its Exploration, Consumption and Prices - Srimarut, Thammarak; Sittisom, Waleerak (International Journal of Energy Economics and Policy, 2020)
The exploration, consumption and prices of crude oil are very important aspects for the enhancement of the economy of any country. Therefore in order to check the impact of these three aspects of crude oil on economic growth of the country, this study has been conducted by the author. Data collection process has been done in Thailand and 26 years data has been accumulated for analysis purpose. Unit root test, co-integration test and VAR model estimation are the most important tests that have been employed in this particular study. The results of all these tests have been discussed in the study in detail. The impacts of exploration, consumption and prices of crude oil as well as population growth and energy consumption have been found to be significant in regard to economic growth. Various theoretical, practical and policy making benefits of these results have been identified and explored by the author all of which point towards the enhancement of economic growth. In addition, the limitations found in the study along with some recommendations have also been described so that the future researchers may consider them and work on them in order to overcome these limitations. Keywords: Economic Growth, Crude Oil Dynamics, Exploration, Consumption, Prices JEL Classifications: F43, E21 DOI: https://doi.org/10.32479/ijeep.10454